Mechanical Thrombectomy for Acute Ischemic Stroke in Octogenarians: A Systematic Review and Meta-Analysis - Zhao, Weisong; Ma, Pengju; Zhang, Ping; Yue, Xuejing (Frontiers in Neurology, 2020)
Background and purpose: Multiple randomized trials have confirmed that mechanical thrombectomy (MT) is an effective treatment method for patients with acute ischemic stroke (AIS). However, evidence on the safety and efficacy of MT in elderly patients compared with younger patients is controversial. This meta-analysis is aimed to systematically compare the outcomes of elderly patients and younger patients after MT for AIS. Methods: A systematical literature search was conducted in the PubMed, EMBASE and Cochrane Library database. The primary outcomes were favorable functional outcome at 90 days and mortality. The secondary outcomes were symptomatic intracerebral hemorrhage (sICH) and successful recanalization rate. Odds ratios (ORs) was estimated using a random effects model. Results: Sixteen studies published between 2014 and 2019 were included in this meta-analysis totally involving 3952 patients. The pooled results showed that patients aged ≥80 years had worse functional outcome (OR=0.41; [95% CI, 0.32-0.51]; P<0.001), and higher rates of mortality (OR=2.26; [95% CI, 1.73-2.95]; P<0.001). There was a trend of higher rates of sICH in patients aged ≥80 years compared with patients aged <80 years, whereas this did not reach statistical significance (OR=1.29; [95% CI, 0.90-1.85]; P=0.17). Furthermore, the frequency of successful recanalization was also lower in patients aged ≥80 years compared with patients aged <80 years (OR=0.70; [95% CI, 0.54–0.92]; P<0.01). The subgroup analysis indicated that, in comparison with those studies published between 2014 and 2016, elderly patients undergoing MT had better outcomes in studies published between 2017 and 2019.Conclusion: Elderly patients undergoing MT had higher risk of mortality and worse functional outcome. Meanwhile, There was a trend towards higher rates of sICH and lower probability of achieving successful recanalization in elderly patients. These findings emphasize the need for improving the rates of successful recanalization in elderly patients with AIS. In addition, advanced technology of endovascular intervention and periinterventional management might be associated with the prognosis in elderly patients. However, more prospective or randomized studies should be conducted to further explore this issue.